Experimental Evaluation Study on High Temperature Tolerance Foam for Profile Control of Steam Huff-n-Puff - Yang Liu; Xiao Yuan; Yu Bao (Geofluids)
In the process of steam huff and puff to develop heavy oil reservoirs, steam channeling is the main factor that restricts the development effect, which causes that the swept area of steam is limited and unable to heat heavy oil adequately. It is important to find an economical and efficient method to prevent steam channeling from happening at steam huff and puff production; thus, a DF-2 high temperature tolerance foam system is proposed to assist steam huff and puff production in this paper. Firstly, utilizing high-temperature aging tank and high-speed stirrer device, the foam quality of DF-2 foam and four kinds of other common industrial foams were evaluated and compared; this experiment result shows that the DF-2 foam has the best temperature tolerance. Whereafter, three groups of single-sandpack experiments were carried out to investigate the change of DF-2 foam resistance factor under different conditions, which included the influence of gas liquid ratio, injection pattern, and crude oil, and the blocking capabilities of DF-2 foam were studied. Through the dual-sandpack experiment, the profile control performance and diversion capacity of the DF-2 foaming agents were studied and evaluated systematically. Finally, the DF-2 high temperature tolerance foam agent was applied to on-site production. The sandpack experiment results indicated that the resistance factor of DF-2 foam agent decreased with gas-liquid ratio, and the optimal gas-liquid ratio was 1 : 1. Coinjection of gas and liquid with foam generator is better than slug injection. Crude oil in sandpack can reduce blocking capability to some extent. During the application of the DF-2 high temperature tolerance foaming agent in the steam huff-n-puff process in M-12 Oilfield block, it had a good performance of profile control and foam blocking, solving the problem of steam channeling and improving the steam sweep area to increase the steam-oil ratio in the heavy oil reservoir, and the production performance of steam huff and puff was improved to a great extent.